The Wiley handbook of human computer interaction set (Hoboken, NJ : John Wiley & Sons, 2018)
Once, human-computer interaction was limited to a privileged few. Today, our contact with computing technology is pervasive, ubiquitous, and global. Work and study is computer mediated, domestic and commercial systems are computerized, healthcare is being reinvented, navigation is interactive, and entertainment is computer generated. As technology has grown more powerful, so the field of human-computer interaction has responded with more sophisticated theories and methodologies. Bringing these developments together, The Wiley Handbook of Human-Computer Interaction explores the many and diverse aspects of human-computer interaction while maintaining an overall perspective regarding the value of human experience over technology.
Keywords: Human-computer interaction